Ergebnisse der 4. Fachtagung Bewegungstherapie 2023. Digital - Was und wie viel? - Streber, Rene; Bestmann, Anja; Brüggemann, Silke; Göhner, Wiebke; Heimsoth, Jörg; Kinkel, Stephan; Peters, Stefan; Pfeifer, Klaus; Reusch, Andrea; Schaller, Andrea; Sudeck, Gorden; Geidl, Wolfgang (4. Fachtagung Bewegungstherapie 2023, 2023)
Digital technologies and applications offer multiple potentials to optimize the care of individuals with chronic, non-communicable diseases. This is particularly applicable to exercise therapy in the context of medical rehabilitation and aftercare. However, successful exploration and utilization of the diverse scenarios throughout the rehabilitation process depends on several prerequisites and conditions. The perspectives of the exercise therapists on the multifaceted process of increasing digitalization in rehabilitation were hardly highlighted. Against this background, the topic of digitalization in exercise therapy in the context of medical rehabilitation was taken up at the 4th symposium on exercise therapy 2023 under the theme: “Digital – What is it and how much of it?”. The objective was to promote a multi-perspective and scientifically based discussion, to explore potentials and application areas, risks and limits as well as questions of implementation regarding digitalization in exercise therapy with the participating exercise therapists in an interactive workshop format with the motto: “Shaping new paths in exercise therapy”. This article presents the results and documentation of the 4th Symposium on Exercise Therapy 2023. Participants identified scenarios for the phases before, during and after rehabilitation. It is apparent that digitalization can support a wide range of organizational, administrative and therapeutic processes. However, the main focus should be on the professions and patients involved in rehabilitation. Similarly, the fears and reservations of the respective actors should be recognized and specifically addressed. With regard to implementation and the resources required for this purpose, the results were elaborated in a structured manner on the basis of four perspectives: Rehabilitants, therapists, technology, and rehabilitation facility and system. These results of the 4th Symposium on Exercise Therapy form an important orientation point for the upcoming digitization processes in medical rehabilitation with a special focus on exercise therapy. They can contribute to a systematic quality development process of exercise therapy supported by digital elements in the context of medical rehabilitation.<br
Keywords: Bewegungstherapie; Digitale Transformation; Digitalisierung; Rehabilitation